Menuju Pembukuan Secara Akuntabel dan Konsisten - Listya Sugiyarti; Effriyanti Effriyanti (S1 Accounting Program, Universitas Pamulang, 2020)
Community service by lecturers and academics who have qualified knowledge can be done to the public at any level, to provide solutions to problems faced with the aim of future improvement. The purpose of community service activities in the playgroup & kindergarten Little Bee House with the concept of